Relationship between diagnostic accuracy of microRNAs for NSCLC and number of combined microRNAs: an overview with meta-analysis. (2nd September 2021) - Li, Muyang; Gao, Ya; Shi, Jiyuan; Zhang, Yi; Zhang, Mei; Tian, Jinhui
ABSTRACT: Objective : Several systematic reviews (SRs) have assessed the diagnostic accuracy of microRNAs (miRNAs) for NSCLC, and this overview aimed to assess the relationship between diagnostic accuracy of miRNAs for NSCLC and number of microRNAs combinations. Methods : Embase.com, PubMed, the Cochrane Library, and Web of Science were searched. The PRISMA-DTA was used for reporting quality evaluation. Meta-analysis was conducted to assess the pooled diagnostic accuracy of different miRNAs combinations, and subgroup analyses were performed based on the source of miRNA. Results : Fourteen SRs with 91 original studies were included. Three SRs had minimal reporting flaws, and 11 SRs had medium flaws. The pooled sensitivity and specificity were 0.76 and 0.80 for single miRNA, 0.80 and 0.81 for two miRNAs combined, 0.82 and 0.88 for three miRNAs combined, 0.88 and 0.92 for four miRNAs combined, 0.87 and 0.87 for five miRNAs combined, and 0.87 and 0.89 for six or more miRNAs combined. And miR-21 was mostly appeared. Subgroup analyses suggested that the serum-derived miRNA had the relatively best diagnostic value compared to other sources. Conclusions : Future studies should explore specific and serum-derived miRNAs in NSCLC and combine them to improve the diagnosis accuracy of NSCLC, which had great significance in economic efficiency.